Functional Domains, Functions, and the Notion of Complexity: The Systems of Reference - Frajzyngier, Zygmunt (Frontiers in Communication, 2021)
Abstract The present study addresses the issues of (1) how to define complexity in the study of functions, (2) how to measure complexity in the study of functions, and (3) the benefits of the notion of semantic complexity in the analysis of language. This argues for a metric of complexity narrowed to single domains, something that has been already mentioned in some other studies. Such measures of complexity can then point to areas of further studies, both synchronic and diachronic. Two metrics of complexity are proposed: The first one involves the number of functions encoded in the given domain. The second is the number of functions that the speaker needs to take into consideration in realizing the functions encoded in the given domain. The argumentation for the proposed approach to complexity is based on cross-linguistic examination of the systems of reference of languages belonging to different families. The implication of this study is that the complexity of functional domains is the fundamental motivation of the complexity of the formal means of coding.